Passive Restoration of the Mountain Fens of the Caltho‑Alnetum Community in the Babia Góra National Park - Nicia, Paweł; Bejger, Romualda; Sterzyńska, Maria; Zadrożny, Paweł (Geomatics and Environmental Engineering, 2020)
Hydrogenic habitats play important ecological roles, particularly in mountain areas. In mountain areas, surface layers typically contain large concentrations of organic matter and are capable of accumulating large volumes of water. This has a positive impact on water management. Due to its specific properties, the soil in hydrogenic habitats supports many rare and often listed species of fauna and flora. Such hydrogenic habitats include: low sedge mountain fens and mountain fens of the Caltho‑Alnetum community which, despite their limited areas, have a positive impact on biodiversity. In the 20th century, drainage due to land use changes caused the degradation of many such habitats. As a result, soils from the organic matter accumulation phase entered the decay phase. A consequence of the change in habitat conditions is the extinction of many plant and animal species of narrow ecological amplitude, usually classified as stenotopic species. To prevent the degradation of hydrogenic habitats, it is necessary to start their restoration processes, which should be the most effective and possibly least intrusive. The work discusses both the methodology and restoration procedures of selected degraded habitats of mountain fen of the Caltho‑Alnetum community in the Babia Góra National Park and presented the impact of those procedures on the water levels.